Comparative Effectiveness of Haruan and Salmon Fish Extracts in Preventing Stunting Among Toddlers: A Quasi-Experimental Study - Warastuti, Widya; Ariestini, Tri Ratna; Rahmawati, Fetty; Elisa, Elisa (Journal of Applied Nursing and Health, 2025)
Background: Stunting, a condition characterized by impaired growth and short stature in toddlers resulting from chronic malnutrition, remains a primary health concern in Indonesia, including Central Kalimantan. A significant contributing factor is the inadequate consumption of animal protein. Fish, such as haruan (Channa striata) and salmon, are excellent sources of protein and essential nutrients crucial for growth. However, comparative studies examining the efficacy of the local haruan fish extract and imported salmon fish extract in preventing stunting are scarce. This study aims to compare the effectiveness of these two fish extracts among toddlers in the operational area of the Pahandut Community Health Center, Palangka Raya City. Methods: This quasi-experimental study followed TREND reporting guidelines. The study involved 100 toddlers, selected by purposive sampling based on specific inclusion/exclusion criteria. Participants were divided into two groups: one group receiving haruan fish extract and the other group receiving salmon extract. The intervention was conducted for three months (June to August 2023). Anthropometric measurements of mid-upper arm circumference (MUAC), body length, and body weight were taken monthly. Data were analyzed using the Wilcoxon Signed-Rank Test and the Mann-Whitney U Test. Results: The Wilcoxon Signed-Rank Test showed that both haruan and salmon fish extracts significantly increased MUAC, Body Length, and Body Weight in each group (p < 0.001). The average increase in MUAC was 0.8 cm for the haruan group and 0.9 cm for the salmon group. However, the Mann-Whitney U Test did not show a statistically significant difference between the two treatment groups in terms of increases in MUAC (p = 0.452) and Body Weight (p = 0.387). These findings indicate that both extracts are equally effective in improving the nutritional status of stunted children. Conclusion: Haruan and salmon fish extracts are equally effective in improving the anthropometric status of stunted toddlers, suggesting that locally sourced haruan can serve as a cost-effective, sustainable alternative to imported salmon in stunting prevention programs.